Sex-ratio among childhood cancers by single-year of age - Williams, Lindsay A (Pediatr Blood Cancer, 2019)
BACKGROUND: The male excess in childhood cancer incidence is well established; however, the underlying biologic mechanisms remain unknown. Examining the association between male sex and childhood cancer by single year of age by tumor type may highlight important periods of risk such as variation in growth and hormonal changes, which will inform etiologic hypotheses. METHODS: Using data from the Surveillance, Epidemiology and End Results (SEER) 18 registries (2000–2015), incidence rate ratios (IRR) and 95% confidence intervals (95% CI) were estimated as the measure of association between male sex and childhood cancer by single year of age (0–19). RESULTS: The IRR for male cancer overall was 1.19 (95% CI: 1.18–1.20) and was similar in magnitude at nearly every year of age. Burkitt lymphoma was strongly associated with male sex (IRRs ≥2 at each year of age). Increased incidence was observed among males for acute lymphoblastic leukemia, Hodgkin and Non-Hodgkin lymphomas for nearly all years of age. Medulloblastoma was the only central nervous system tumor with a significant male predominance at nearly every age. Male sex displayed a consistent inverse association with nephroblastoma and thyroid carcinoma over the ages studied. CONCLUSIONS: Male sex was positively associated with most cancers. The higher incidence rates observed in males remained consistent over the childhood and adolescent periods suggesting that childhood and adolescent hormonal fluctuations may not be the primary driving factor for the sex disparities in childhood cancer. The observed incidence disparities may be due to sex differences in exposures, genetics, or immune responses.